New Directions in Western Soteriology - Bloor, Joshua D. A. (Theology, 2015)
Traditionally, the doctrine of deification has been embraced significantly in the Eastern tradition. Though glimpses of it can be found throughout Western Christendom, it has often been cast out and labelled as sacrilegious Greek myth. This article however, will seek to prove that, amid contemporary Western theological discourse, deification has experienced a renewed sense of appreciation and appropriation. As well as examining contemporary theologians over the last few decades – from a broad spectrum of Christian traditions – this article will also touch on the brief history of the doctrine, as well as the Western hesitation which the doctrine has received.